2005
DOI: 10.1111/j.1365-2141.2005.05521.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose thalidomide in combination with oral weekly cyclophosphamide and pulsed dexamethasone is a well tolerated and effective regimen in patients with relapsed and refractory multiple myeloma

Abstract: SummaryThe feasibility and efficacy of a triple regimen of oral weekly cyclophosphamide, monthly pulsed dexamethasone and low-dose Thalidomide (CDT) was studied in 52 patients with relapsed or refractory multiple myeloma (MM). All 52 patients were evaluable for response with a median follow up of 18 (4-29) months. About 17% achieved complete response (CR), 62% partial response (PR), 11% minimal response (MR), 6% stable disease (SD) and 4% progressive disease (PD), resulting in an objective response rate ( ‡MR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(49 citation statements)
references
References 46 publications
2
47
0
Order By: Relevance
“…Combining thalidomide with dexamethasone improves its efficacy in relapsed MM and phase II studies have reported an ORR of 41-56%. 59,60 The efficacy is further improved when thalidomide is used in triple or even quadruple combinations, including thalidomide with dexamethasone and bortezomib (VTD), dexamethasone and cyclophosphamide (CTD), bortezomib plus melphalan and prednisone (VMPT) or dexamethasone (VMDT), lenalidomide, melphalan and prednisone (RMPT), or VTD with pegylated liposomal doxorubicin. 23,[61][62][63][64][65][66] These regimens have been associated with an ORR of 63-90% with CR being reported in 2-35% of patients.…”
Section: Thalidomidementioning
confidence: 99%
“…Combining thalidomide with dexamethasone improves its efficacy in relapsed MM and phase II studies have reported an ORR of 41-56%. 59,60 The efficacy is further improved when thalidomide is used in triple or even quadruple combinations, including thalidomide with dexamethasone and bortezomib (VTD), dexamethasone and cyclophosphamide (CTD), bortezomib plus melphalan and prednisone (VMPT) or dexamethasone (VMDT), lenalidomide, melphalan and prednisone (RMPT), or VTD with pegylated liposomal doxorubicin. 23,[61][62][63][64][65][66] These regimens have been associated with an ORR of 63-90% with CR being reported in 2-35% of patients.…”
Section: Thalidomidementioning
confidence: 99%
“…The regimen containing cyclophosphamide, thalidomide, and dexamethasone was well tolerated and effective in patients with relapsed MM, achieving ORR of 83-90% [16,17]. The combination of cyclophosphamide, bortezomib, and dexamethasone induced ORR in up to 75% of refractory or relapsed MM patients [15].…”
Section: Discussionmentioning
confidence: 94%
“…In refractory or relapsed myeloma, combinations including thalidomide or bortezomib with dexamethasone and cyclophosphamide have been extensively investigated [14][15][16][17][18]. The regimen containing cyclophosphamide, thalidomide, and dexamethasone was well tolerated and effective in patients with relapsed MM, achieving ORR of 83-90% [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32] Please see Table 1 for a summary of studies evaluating thalidomide-alkylator combinations. Overall, the available data suggest that the risk of TEE for patients with NDMM is similarly increased whether they are being treated with concurrent MPT or TD, whereas the risk for RRMM patients receiving thalidomide-cyclophosphamide combination therapy is minimally, if at all, increased over baseline.…”
Section: Thalidomide Plus Cytotoxic Chemotherapymentioning
confidence: 99%